Fast and Simple Chemical Fingerprinting Analysis of Medicinal Herbs by Paper Cone Spray Ionization Mass Spectrometry (PCSI MS). (22nd July 2016) - Jun, Gyuwoong; Park, Tae‐Min; Cha, Sangwon
Abstract : Paper cone spray ionization (PCSI), an extractive ambient ionization method that is specialized for raw solid material analysis, was applied to chemical fingerprinting analysis of raw medicinal herbs. Experimental parameters of PCSI mass spectrometry (MS) were first optimized against Salvia miltiorrhiza Bunge (danshen). Our results showed that simple alkyl alcohols, such as methanol and 2‐propanol, generally worked well in both polarities and could generate representative chemical fingerprints instantly for a given herbal sample. In addition, in situ extraction from untreated herbal slices during PCSI MS was found to be enough to generate characteristic chemical signatures of a given medicinal herb. After optimization, representative fingerprints of various medicinal herbs, including Sophora flavescens (kushen) and Paeonia lactiflora Pall (shaoyao), were successfully obtained by PCSI MS. In addition, morphologically similar herbs, Cynanchum auriculatum and Cynanchum wilfordii, could be differentiated from each other by their chemical signatures by PCSI MS. Abstract :